Answer:
63 mils
Step-by-step explanation:
The equation for the parabola would be:
and ![y=6](https://tex.z-dn.net/?f=y%3D6)
use the second expression to calculate the left-hand side of the first equation:
![4\cdot 6 = 2x -10\\24 = 2x -10](https://tex.z-dn.net/?f=4%5Ccdot%206%20%3D%202x%20-10%5C%5C24%20%3D%202x%20-10)
Add 10 to both sides if this equation to get
![34 = 2x](https://tex.z-dn.net/?f=34%20%3D%202x)
and divide both sides by 2
![17 = x](https://tex.z-dn.net/?f=17%20%3D%20x)
this proves that x = 17, give the two initial equations
Answer:
y=−15
Hope this helps! Please mark Brainliest!